Eosinophilic Solid and Cystic Renal Cell Carcinoma With Melanin Pigment-Expanding the Morphological Spectrum - Aldera, Alessandro Pietro; Hes, Ondřej (International journal of surgical pathology, 2022)
Eosinophilic solid and cystic renal cell carcinoma (ESC-RCC) is an emerging entity in renal neoplasia with distinctive histopathological findings and a generally favorable prognosis. The presence of melanin pigment in a renal tumor typically prompts the observer to consider the microphthalmia-associated transcription family translocation renal cell carcinomas. We present a renal tumor occurring in a 19-year-old male patient which had the typical morphology of ESC-RCC but showed the additional finding of focal melanin pigment. This tumor showed strong and diffuse positive immunolabeling with paired box gene 8 and cytokeratin 20, and was negative with epithelial membrane antigen, carbonic anhydrase 9, CD117, cytokeratin 7, and transcription factor E3. Human melanoma black-45 showed focal positivity, but Melan-A was negative. Next-generation sequencing revealed a mutation in the TSC2 gene (c.4490C > G, p.[Pro1497Arg] and c.1257 + 1del) and break apart fluorescence in-situ hybridization with TFE3 and TFEB probes was negative. In this case report, we present the novel finding of melanin pigment occurring in a genetically proven and otherwise typical ESC-RCC, and briefly discuss the differential diagnostic considerations.
Keywords: mutace; dospělí; kidney tumor; Adult; TFE3; mladý dospělý; melaniny; Melanins; lidé; Translocation, Genetic; immunohistochemistry; karcinom z renálních buněk; Mutation; Kidney Neoplasms; Carcinoma, Renal Cell; Male; nádorové biomarkery; genitourinary pathology; Young Adult; nádory ledvin; Biomarkers, Tumor; hybridizace in situ fluorescenční; TSC; melanin pigment; mužské pohlaví; translokace genetická; In Situ Hybridization, Fluorescence; renal cell carcinoma; Humans